A Qualitative Study of the Pathways Into and Impacts of Family Homelessness. (June 2018) - Sylvestre, John; Kerman, Nick; Polillo, Alexia; Lee, Catherine M.; Aubry, Tim; Czechowski, Konrad
Homelessness has consequences for families, including risk of deterioration in the health of their members, disruption of family dynamics, and separation of parents and children. This study used qualitative interviews to explore pathways into and perceived consequences of homelessness among 18 families living in an emergency family shelter system in Canada. Findings showed that families' experiences prior to their homelessness were characterized by vulnerability, instability, and isolation. In the emergency shelter system, families faced new challenges in environments that were restrictive, noisy, chaotic, and afforded little privacy. Participants described a further disruption of relationships and described having to change their family practices and routines. Despite the challenges that families encountered, some participants felt optimistic and hopeful about the future. Future research is needed on ways in which shelters can be more hospitable, supportive, and helpful for parents and their families to minimize negative impacts and facilitate timely rehousing of families.